2017
DOI: 10.1021/acsami.7b13346
|View full text |Cite
|
Sign up to set email alerts
|

Fully Coated Semitransparent Organic Solar Cells with a Doctor-Blade-Coated Composite Anode Buffer Layer of Phosphomolybdic Acid and PEDOT:PSS and a Spray-Coated Silver Nanowire Top Electrode

Abstract: In the aim to realize high performance semitransparent fully coated organic solar cells, printable electrode buffer layers and top electrodes are two important key technologies. An ideal ink for the preparation of the electrode buffer layer for printed top electrodes should have good wettability and negligible solvent corrosion to the underlying layer. This work reports a novel organic-inorganic composite of phosphomolybdic acid (PMA) and PEDOT:PSS that features excellent wettability with the active layer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 71 publications
(120 reference statements)
1
56
0
Order By: Relevance
“…[ 14,17,30 ] Currently, the best polymer donor reported for collocating NFAs requires an extremely deep highest occupied molecular orbital ( HOMO ) level that is more negative than −5.4 eV to maximize the built‐in voltage of devices. [ 9–11,16,17,31 ] The low HOMO level of the active layer therefore forms a massive energy barrier between the HOMO of the electron donor and the work function (WF) of PEDOT:PSS (WF ≈ −5.0 eV is mostly reported in the literature), [ 32–34 ] which results in the poor electrical performance of inverted devices. Nevertheless, only a few studies have reported an inverted OPV device using an NF‐based BHJ layer with an alternative solution‐processed HTL for industrial module production.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,17,30 ] Currently, the best polymer donor reported for collocating NFAs requires an extremely deep highest occupied molecular orbital ( HOMO ) level that is more negative than −5.4 eV to maximize the built‐in voltage of devices. [ 9–11,16,17,31 ] The low HOMO level of the active layer therefore forms a massive energy barrier between the HOMO of the electron donor and the work function (WF) of PEDOT:PSS (WF ≈ −5.0 eV is mostly reported in the literature), [ 32–34 ] which results in the poor electrical performance of inverted devices. Nevertheless, only a few studies have reported an inverted OPV device using an NF‐based BHJ layer with an alternative solution‐processed HTL for industrial module production.…”
Section: Introductionmentioning
confidence: 99%
“…At a low voltage bias, traps in the active layer can respond to the modulated signal, whereas at a high voltage bias, the trap state can suppress the response. [ 98,99 ] The Nyquist plots from EIS measurements are shown in Figure 15b. These plots were fitted with an equivalent electrical circuit, which is shown in Figure 15b for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Encouraged by these findings, the approach reported by Ji et al was attempted. Thus, 0.8 mL of PEDOT388, 0.1 mL of MoPMo solution, and 0.1 mL of isopropanol have been mixed and used as a composite deposited by spin coating.…”
Section: Resultsmentioning
confidence: 99%
“…This issue is commonly not tackled in the routine laboratory‐scale practice, thus it is essential to stress the importance of a thick HTL for practical applications. Interestingly, either molybdenum salts, molybdenum oxide nanoparticles, or Mo‐polyoxometallates have also been mixed with PEDOT:PSS to provide hybrid buffer layers. Inverted polymer solar cells show efficiencies comparable with e‐MoO x and satisfactory stability …”
Section: Introductionmentioning
confidence: 99%